Glycosylation is necessary for the correct folding of human immunodeficiency virus gp120 in CD4 binding. - Li, Y (1993)
Conflicting results have been reported regarding the role of carbohydrate on human immunodeficiency virus (HIV) envelope glycoprotein gp120 in CD4 receptor binding. Glycosylated, deglycosylated, and nonglycosylated forms of HIV type 1 (HIV-1) and HIV-2 gp120s were used to examine CD4 receptor-binding activity. Nonglycosylated forms of gp120 generated either by deletion of the signal sequence of HIV-1 gp120 or by synthesis in the presence of tunicamycin failed to bind to CD4. In contrast, highly mannosylated gp120 bound to soluble CD4 molecules well. Enzymatic removal of carbohydrate chains from glycosylated gp120 by endoglycosidase H or an endoglycosidase F/N glycanase mixture had no effect on the ability of gp120 to bind CD4. An experiment which measured the ability of gp120 to bind to CD4 as an assay of the proper conformation of gp120 showed that carbohydrate chains on gp120 are not required for the interaction between gp120 and CD4 but that N-linked glycosylation is essential for generation of the proper conformation of gp120 to provide a CD4-binding site.